RADIOLOGICAL DIAGNOSIS OF FATTY LIVER AND HEPATOMEGALY IN KSA - Ibrahim Hudaid Almutairi1, Mohammad Awadh Alharbi2, Faisal Miqad Alharbi3, Ali Saeed Alqarni4, Trad Hamed Almutairi5, Faisal Abdu Moafa6, Majed Dakhilallah Almutairi7, Faisal Rafe Almutairi8 (Chelonian Research Foundation, 2023)
Background: Fatty liver disease (FLD), whether it is alcoholic FLD (AFLD) or nonalcoholic FLD (NAFLD), encompasses a morphological spectrum consisting of hepatic steatosis (fatty liver) and steatohepatitis. CT scans provide a non-invasive means of diagnosing the presence and severity of NAFLD. Objective: to estimate the prevalence of diffuse fatty liver disease and if there a relationship between diffuse fatty liver disease and hepatomegaly, among patients under routine CT scan different Hospitals in Saudi Arabia. Methods: It was a cross sectional study. We examined 158 adults aged 21-55 years, with mean age (±SD) of was 41.55 (±9.08). They attend the radiology department for routine CT scanning KUB, all cases with poor quality scan was not included. A chick list was used in data collection, it contains; age, sex, fatty liver (HU<40), hepatic density and liver size (in cm). Results: about tow thirds of the studied participants (63.9%) were males. Fatty liver (HU<40) was found in 24 (15.2%) of the studied participants. Hepatic density measured by Hounsfield Unit (HU) was < 40 HU in 15.2% and > 40 HU in 84.8%. Liver size (in Cm) was 15-18 (hepatomegaly) in 17.7% and ≤ 15 in 82.3% of the studied participants. the relation between sex and fatty liver was insignificant (P>0.05). The majority (41.7%) of fatty liver cases were from the age group 31-40 years, then 33.3% from 41-50 years but the relation between age and fatty liver was also insignificant (P>0.05). More than 2 thirds (70.8%) of fatty liver cases had hepatomegaly (liver size 15 -18Cm) and the relation between fatty liver and liver size was highly significant (P<0.01). Conclusion: The use of liver attenuation values will be useful to assess the diagnosis of Fatty liver and hepatomegaly, so it is a reliable device in further studies as in follow up of the same participants. Key words: Computed Tomography, Fatty Liver, Hepatomegaly, Saudi Arabia.